2023
DOI: 10.1186/s43141-023-00509-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, partial purification, and characterization of a novel high molecular weight alkaline protease produced by Halobacillus sp. HAL1 using fish wastes as a substrate

Abstract: Background Hydrolytic enzymes from halophilic microorganisms have a wide range of industrial applications. Herein, we report the isolation of Halobacillus sp. HAL1, a moderately halophilic bacterium that produces a novel high molecular weight extracellular alkaline protease when grown in fish processing wastes as a substrate. Results Results showed that the isolated strain belonged to the genus Halobacillus, and it was designated as Halobacillus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Studying the impact of different temperatures (20, 25, and 30 °C) revealed that the maximum enzyme production was obtained at 25 °C. These results align with findings reported by Pansuriya et al and Fahmy et al, both of whom observed maximum protease production at 25 °C [ 47 , 49 ]. The hydrogen ion concentration promotes microbial growth and product formation by regulating the transport of various metabolites and nutrients across the cell membrane [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Studying the impact of different temperatures (20, 25, and 30 °C) revealed that the maximum enzyme production was obtained at 25 °C. These results align with findings reported by Pansuriya et al and Fahmy et al, both of whom observed maximum protease production at 25 °C [ 47 , 49 ]. The hydrogen ion concentration promotes microbial growth and product formation by regulating the transport of various metabolites and nutrients across the cell membrane [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hence, our findings suggest that silkworm pupae offer an alternative source of carbon and nitrogen suitable for use in the fermentation process [26,43]. Several previous studies have indicated that the use of agro-industrial residues can enhance the production of proteases [31,[44][45][46][47]. Additionally, enzyme production can benefit from the presence of nutritional sources and the overall growth and metabolism of the microbial strain [4,5,14].…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations